PEROXIDASE ACTIVITY AS AN INDICATOR OF WATER STRESS IN SWEET PEPPER PLANTS - Klar, Antonio Evaldo; Jadoski, Sidnei Osmar; Lima, Giusepina Pace Pereira (IRRIGA, 2006)
PEROXIDASE ACTIVITY AS AN INDICATOR OF WATER STRESS IN SWEET PEPPER PLANTS Antonio Evaldo Klar1; Sidnei Osmar Jadoski2; Giusepina Pace Pereira Lima3 1Departamento de Engenharia Rural, Faculdade de Ciências Agronômicas, Universidade Estadual Paulista, Botucatu, SP, klar@fca.unesp.br. 2Universidade Estadual do Centro Oeste, Centro de Ciências Agrárias e Ambientais, Guarapuava, Pr 3Departamento de Bioquímica, Faculdade de Ciências Agronômicas, Universidade Estadual Paulista, Botucatu, SP 1 ABSTRACT The purpose of the study was to evaluate the physiological and biochemical behavior of sweet pepper (Capsicum annuum L.) plants under different soil water availability conditions and the efficiency of the peroxidase (EC. 1.11.1.7) activity as an indicator of water stress in plants. The experiment was carried out at the Faculdade de Ciências Agronômicas – UNESP, Botucatu, SP. Sweet pepper plants were grown for 230 days after transplanting of seedlings and arranged in a completely randomized experimental design with 4 treatments, two irrigation managements (50 and 1500 kPa) and two soil surface managements (presence or absence of black polyethylene covering), and six replications. Physiological activities, such as stomatal transpiration and resistance to water vapor diffusion, were evaluated as well as biochemical activities, such as peroxidase activity and total soluble protein in foliar tissues. It was observed that soil water availability may lead to physiological and biochemical alterations in plants. Successive water stress cycles may promote the development of characteristics responsible for improving plant tolerance to periods of low water availability. The peroxidase enzyme activity showed to be an efficient indicator of water stress in sweet pepper plants. KEYWORDS: enzymatic activity; soil moisture; vegetable physiology; soluble protein; Capsicum annuum L. KLAR, A. E.; JADOSKI, S. O.; LIMA, G. P. P. A PEROXIDASE COMO INDICADOR DE DÉFICITS HÍDRICOS EM PLANTAS DE PIMENTÃO. 2 RESUMO O objetivo do presente estudo foi avaliar o comportamento fisiológico e bioquímico do pimentão (Capsicum annuum L) sob diferentes condições de disponibilidade de água no solo, além da eficiência da peroxidase (EC 1.11.1.7) como indicador de déficits hídricos nas plantas. O experimento foi desenvolvido na Faculdade de Ciências Agronômicas – UNESP, Botucatu, SP, durante 230 dias após o transplante das plântulas em condições de ambiente protegido com quatro tratamentos: dois níveis de irrigação (-50 e – 1500 kPa como potenciais mínimos de água do solo) e dois manejos de cobertura do solo (com e sem cobertura de lonas de polietileno preto) com seis repetições. As atividades fisiológicas, como a resistência difusiva dos estômatos e a transpiração foram avaliadas, assim como a peroxidase e a proteina solúvel, nos tecidos foliares. Os resultados mostraram que os déficits hídricos alteraram os fatores fisiológicos estudados e promoveram respostas positivas para a tolerância à déficits hídricos. A peroxidase mostrou ser um eficiente indicador de estresse hídrico em plantas de pimentão. UNITERMOS: irrigação, cobertura morta, potencial de água no solo, proteina solúvel.